Solitary Fibrous Tumor of the Kidney Developing Local Recurrence - Wataru Usuba; Hideo Sasaki; Hidekazu Yoshie; Kazuki Kitajima; Hiroya Kudo; Ryuto Nakazawa; Yuichi Sato; Masayuki Takagi; Tatsuya Chikaraishi (Case Reports in Urology)
Solitary fibrous tumor (SFT) of the kidney is a rare entity and usually displays a favorable prognosis. We herein report a second case of renal SFT developing local recurrence. A 50-year-old man was referred to our hospital because of a left renal mass. An abdominal CT detected a large renal tumor and radical nephrectomy was performed with a possible diagnosis of renal cell carcinoma. The resected tumor size was measured at 17 × 11 × 8 cm. Grossly, necrosis was observed in central lesion of the tumor but hemorrhage was not observed. Microscopically, the tumor consisted of spindle-shaped cells with scant cytoplasm accompanied by hyalinized collagenous tissue, which displayed hemangiopericytomatous patterns. The cellularity was normal and nuclear pleomorphism was not observed. Ki-67 labeling index was less than 3%. The pathological diagnosis of SFT was made without obvious malignant findings. Three years after the surgery, a follow-up CT scan detected a mass lesion in the tumor bed. Surgical resection was performed and the resected tumor was compatible with local recurrence of the SFT without obvious malignant findings. Renal SFT should be carefully monitored even in the absence of obvious malignant findings.